LekLink - Scheduling Lecture Links and Lecture Capture for Academics - W.A.A.D. Wijesingha,; D.P.N. Athulathmudali,; V.C. Gallage,; P.R.T.S.P. Perera,; D. I. De Silva,; Piyumika Samarasekara, (International Journal of Engineering and Management Research, 2022)
This paper discusses the development of a lecture link and content management system that enables more specific lecture content and link management functionalities. With this software, every user can easily access their lecture links and information. The MERN stack was utilized in the creation of this system. Under the MERN Stack, we used Express.js for the back end, React.js for the front end, MongoDB as the database system, and Node.js as the testing environment for the local system development. With the assistance of Rest APIs and services, we have created the following application with enhanced performance and user interfaces that facilitate interaction with the system. The user is not required to create a separate meeting connection for material distribution in this system. As a result of implementing a service with API access points for generating lecture links, it is possible to handle everything with only a few clicks. Additionally, users can manage their recorded lecture materials using this system. With the suggested approach, any academic institution can easily manage its content.